THE USE OF SONG LYRICS THROUGH VIDEO CLIP TO INCREASE ENGLISH VOCABULARY MASTERY (CLASSROOM ACTION RESEARCH AT SMP BRAWIJAYA) - Sakinah, Yanik Lailinas (Balai Bahasa Kalimantan Tengah, 2018)
The first thing should be mastered by learners for learning a foreign language is vocabulary. Vocabulary is a foundation besides pronunciation and grammar for the learners. The result of the preliminary study at SMP Brawijaya Smart School for the seventh B students showed that the students had a problem in mastering vocabulary. It can be seen from the results of pre-test and interview with the English teacher. In this case, the researcher tried to increase their vocabulary by using song lyrics through the video clip. The method used in this research is Classroom Action Research (CAR) based on McTaggart’s theory which consisted of four stages in one cycle. They are planning, acting, observing and reflecting. This research was conducted in one cycle and consisted of three meetings to give the students’ treatment by using song lyrics through the video clip. The criteria of success were 70% of the seventh B students reached equal or more than 75 (minimum passing grade). For collecting the data, the researcher used the interview guide, observation sheet, observation checklist, field-notes, questionnaires, and test. The result of this research showed that the vocabulary of the students increased by using song lyrics through video clip as a media in teaching and learning. The percentage showed that 76,19% of students passed the criteria of success. Sixteen students got equal or more than 75 as the minimum passing grade. It can be concluded that the implementation of video clips was successful and effective to increase the students’ vocabulary.Penggunaan Lirik Lagu melalui Klip Video untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris (Penelitian Tindak Kelas di SMP Brawijaya)Hal pertama yang harus dikuasai oleh pelajar untuk belajar bahasa asing adalah kosakata. Kosakata adalah fondasi selain pengucapan dan tata bahasa untuk pelajar. Hasil studi pendahuluan di SMP Brawijaya Smart School untuk siswa kelas VII B menunjukkan bahwa siswa memiliki masalah dalam menguasai kosakata. Hal ini dapat dilihat dari hasil prates dan hasil wawancara guru bahasa Inggris. Dalam hal ini peneliti ingin meningkatkan kosakata siswa menggunakan lirik lagu melalui klip video. Metode yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK) berdasarkan teori dari McTaggart yang terdiri dari empat tahapan dalam satu siklus, yaitu perencanaan, pelaksanaan, pengamatan, dan refleksi. Penelitian ini dilakukan dalam satu siklus dan terdiri atas tiga pertemuan untuk memberikan siswa pembelajaran dengan menggunakan lirik lagu melalui klip video. Kriteria keberhasilan dalam penelitian ini adalah 70% dari siswa kelas B mendapatkan nilai 75 (minimum kelulusan) atau lebih. Untuk mengumpulkan data, peneliti menggunakan wawancara, lembar pengamatan, daftar pengamatan, catatan lapangan, angket, dan tes. Hasil penelitian ini menunjukkan bahwa kosakata siswa meningkat dengan menggunakan lirik lagu melalui klip video sebagai media dalam proses belajar mengajar. Persentase menunjukkan bahwa 76,19% dari jumlah siswa berhasil mencapai kriteria keberhasilan. Ada enam belas siswa yang mendapatkan nilai 75 atau lebih. Jadi, dapat disimpulkan bahwa penggunaan klip video sebagai media pembelajaran sukses dan efektif untuk meningkatkan kosakata siswa